Design of a Proton Exchange Membrane Electrolyzer - Torsten Berning (Hydrogen, 2025)
A novel design of a proton exchange membrane electrolyzer is presented. In contrast to previous designs, the flow field plates are round and oriented horizontally with the feed water entering from a central hole and spreading evenly outward over the anode flow field in radial, interdigitated flow channels. The cathode flow field consists of a spiral channel with an outlet hole near the outside of the bipolar plate. This results in anode and cathode flow channels that run perpendicular to avoid shear stresses. The novel sealing concept requires only o-rings, which press against the electrolyte membrane and are countered by circular gaskets that are placed over the flow channels to prevent the membrane from penetrating the channels, which makes for a much more economical sealing concept compared to prior designs using custom-made gaskets. Hydrogen leaves the electrolyzer through a vertical outward pipe placed off-center on top of the electrolyzer. The electrolyzer stack is housed in a cylinder to capture the oxygen and water vapor, which is then guided into a heat exchanger section, located underneath the electrolyzer partition. The function of the heat exchanger is to preheat the incoming fresh water and condense the escape water, thus improving the efficiency. It also serves as internal phase separator in that a level sensor controls the water level and triggers a recirculation pump for the condensate, while the oxygen outlet is located above the water level and can be connected to a vacuum pump to allow for electrolyzer operation at sub-ambient pressure to further increase efficiency and/or reduce the iridium loading.